Illigeal Dumping Site: Case Study in the District of Johor Bahru Tengah, Johor - Nazerry Rosmady, Rahmat; Abdul Haqi, Ibrahim (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 9th - 12th June 2007 at Park Royal Hotel, Penang.